A Generalized Numerical Approach for Modeling Multiphase Flow and Transport in Fractured Porous Media (Communications in Computational Physics, 2009)
A physically based numerical approach is presented for modeling multiphaseflow and transport processes in fractured rock. In particular, a general frameworkmodel is discussed for dealing with fracture-matrix interactions, which is applicableto both continuum and discrete fracture conceptualization. The numerical modelingapproach is based on a general multiple-continuum concept, suitable for modelingany types of fractured reservoirs, including double-, triple-, and other multiple-continuumconceptual models. In addition, a new, physically correct numerical schemeis discussed to calculate multiphase flow between fractures and the matrix, using continuityof capillary pressure at the fracture-matrix interface. The proposed general modelingmethodology is verified in special cases using analytical solutions and laboratoryexperimental data, and demonstrated for its application in modeling flow throughfractured vuggy reservoirs.